Acting - Greenspon, Jaq (Lincolnwood, Ill. VGM Career Horizons, 1996)
Introduces such careers in the performing arts as actor, singer, comedienne, and writer, using portraits of various people in the field.
Keywords: Theater -- Vocational guidance -- Juvenile literature; Entertainers; Performing arts -- Vocational guidance; Vocational guidance